Role of agricultural engineers in the development of agro - based industries - Abang Ali, Abang Abdullah; Ahmad, Mohammad Nur (1983)
Agro-based industries are important in the ASEAN region, not only from the point of view of demand for increased food supply but also from the need to provide renewable sources of energy and engineering materials. Research and development work in this area are on the increase. Agricultural engineers play an important role in the development of these industries; being trained in engineering and with adequate exposure to the activities in the agricultural sector.